Islamic religious education learning for children at extraordinary middle school for special needs, Sorong city - Sidek, Muhammad; Iribaram, Suparto; Hasbullah, Hasbullah (Program Studi Pendidikan Agama Islam STAI Auliaurrasyidin Tembilahan, 2025)
This study examines the implementation of Islamic Religious Education (IRE) for children with special needs at a public special junior high school in Sorong City. It employs a qualitative descriptive method using observation, interviews, and documentation involving the school principal, two teachers, one parent, and three students with intellectual disabilities, hearing impairments, and autism. The findings indicate that IRE is not taught by specialized IRE teachers but instead by classroom teachers through an internal rotation system, often without formal training in Islamic education or special needs pedagogy. The curriculum is simplified and thematic and does not fully align with the official syllabus. Teaching methods are still dominated by lectures and storytelling without adaptive media. In fact, students respond more positively to visual, practical, and audiovisual learning approaches. The study concludes that IRE instruction has not yet been inclusive and highlights the importance of trained teachers and the development of adaptive teaching materials.